A Self-Detecting and Self-Cleaning Biomimetic Porous Metal-Based Hydrogel for Oil/Water Separation - Li, Zhaoxin; Sang, Shengtian; Jiang, Shuyue; Chen, Liang; Zhang, Haifeng (ACS applied materials & interfaces, 2022)
Porous materials with super-wetting surfaces (superhydrophilic/underwater superoleophobic) are ideal for oil/water separation. However, the inability to monitor the pollution degree and self-cleaning during the separation process limits their application in industrial production. In this study, a porous metal-based hydrogel is proposed, inspired by the porous structure of wood. Porous copper foam with nano-Cu(OH)2 is used as the skeleton, and its surface is coated with a polyvinyl alcohol, tannic acid, and multiwalled carbon nanotube cross-linked hydrogel coating. The hydrogel has superhydrophilicity and excellent oil/water separation efficiency (>99%) and can adapt to various environments. This approach can also realize hydrogel pollution degree self-detection according to the change in the electrical signal generated during the oil/water separation process, and the hydrogel can also be recovered by soaking to realize self-cleaning. This study will provide new insights into the application of oil/water separation materials in practical industrial manufacturing.